Efektifitas Lama Penyinaran Laserpunktur pada Perkembangan Gonad Abalon (Haliotis squamata) Jantan - Agung Setia Abadi; Hendra Budi Kusuma (Jurnal Airaha, 2020)
Now Abaloneis one aquaculture highs economy commodity as a food ingredient. The culture of Abaloneis restrictedin the number ofgonadal maturitybroodstockconsequently there require toimprove gonadal maturity usingLaserpunktur.The research was didinthe FishReproduction laboratoryof FisheriesandMarine SciencesFaculty, BrawijayaUniversity, MalangandBrackish WaterAquacultureCenter(BWAC) Situbondo, EastJava, inAugust -September 2014.The purposeof thisstudywas to determine thegonadal maturityeffect ofLaserpunkturexposureto malesabalone(H. Squamata)parent.Research method be usedexperimental methodwith5treatments and 3 replicated.The treatment exposure process used in treatment A was exposed to the laser point for 50 seconds, the treatment B was exposed to a laser point for 100 seconds, treatment C was exposed to a laser point for 150 seconds, the processing D has been exposed to a laser point of 200 seconds, and K without treatment laser point exposure. The results of the study showed that the best gonadsgrowth occurs on exposed C treatment laser point for 150 seconds.